Princess in love - Cabot, Meg. (New York : HarperTrophy, 2002)
In a series of humorous diary entries, a New York City ninth grader agonizes over her love life, final exams, and future role as the princess of Genovia.
880
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Schools -- Juvenile fiction; Love stories; Diaries -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Humorous fiction